The role of bacterial lipopolysaccharides and gut microbiota dysbiosis in type 1 diabetes - Leino, Linda (My University, 2022)
The definitive etiology of type 1 diabetes (T1D) remains uncertain. However, various studies suggest that gut microbiota dysbiosis might contribute to the development of islet autoimmunity. This risk could be mediated by lipopolysaccharides (LPS), as pro-inflammatory subtypes of gut-derived LPS might prevent the development of T1D through endotoxin tolerance (ET), a state of reduced responsivity to LPS. This thesis aimed to elucidate the differences of lipopolysaccharides from two bacterial species, Escherichia coli and Bacteroides vulgatus, in their capability to stimulate the immune system and to induce ET using the non-obese diabetic mouse model. Of the studied species, B. vulgatus has been associated with T1D and in contrast to E. coli, it synthetizes a weakly agonistic LPS. Acute effects were studied after a single exposure to LPS, whereas ET was modelled with multiple exposures. TNFα production by macrophages was determined with ELISA and T cell and dendritic cell populations were analysed with flow cytometry. Moreover, expression of the chemokine CXCL10 in pancreatic islets was determined with immunofluorescence staining. This study revealed significant functional differences between the two lipopolysaccharides. Unlike B. vulgatus LPS, E. coli LPS efficiently stimulated macrophages to secrete TNFα, activated dendritic cells and induced expression of CXCL10 in the islets. E. coli LPS was also superior to B.vulgatus LPS in tolerizing macrophages, dendritic cells and T cells. Interestingly, tolerization with E. coli LPS reduced the number of diabetogenic CD8+ T cells in vivo. In conclusion, this study demonstrated that certain LPS subtypes might promote the development of islet autoimmunity.
Keywords: type 1 diabetes, dysbiosis, lipopolysaccharide, endotoxin tolerance